1995
DOI: 10.1149/1.2048477
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Microstructure in the Catalyst Layer and Effects of Both Perfluorosulfonate Ionomer and PTFE‐Loaded Carbon on the Catalyst Layer of Polymer Electrolyte Fuel Cells

Abstract: Effects of a perfluorosulfonate ionomer (PFSI) and of a polytetrafiuoroethylene (PTFE) loaded carbon (PTFE-C) on the catalyst layer in the electrode of a polymer electrolyte fuel cell (PEFC) prepared by a new method based on the process of PFSI-colloid formation were investigated by electrochemical techniques and a mercury pore sizer. The microstructure of the catalyst layer and its effect on the PEFC performance were affected by the contents of both PFSI and PTFE-C. The catalyst layer has two distinctive pore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
227
2
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 400 publications
(240 citation statements)
references
References 5 publications
7
227
2
1
Order By: Relevance
“…0, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]However, the optimum N/C ratios are found to be lower, namely 0.7 and 0.5 for the VC and HG supports, respectively. The optimum N/C value using VC as catalyst support is essentially the same as reported by Liu and Song et al [19,20] i.e.…”
Section: Original Research Papermentioning
confidence: 99%
See 2 more Smart Citations
“…0, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]However, the optimum N/C ratios are found to be lower, namely 0.7 and 0.5 for the VC and HG supports, respectively. The optimum N/C value using VC as catalyst support is essentially the same as reported by Liu and Song et al [19,20] i.e.…”
Section: Original Research Papermentioning
confidence: 99%
“…The catalyst support material should have high electronic conductivity, high stability against corrosion, and preferably a mesoporous structure to allow for effective catalyst deposition, fuel access and water management [8]. Uchida [9,10] reported the effects of the microstructure of the catalyst layer on the performance of polymer electrolyte fuel cells (PEFCs) and reported that the pore-size distribution of the carbon support influences the performance of the fuel cell.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The three-phase boundary (TPB), comprising a carbon support with the Pt particles (electron conductor), the ionomer (ion conductor) and the voids (mass transfer), is a key parameter in fuel cell reactions and performance. The pores in the thin film layer can be divided into the primary pores, which exist between catalyst particles (0.02-0.04 μm), and secondary pores, which exist between the agglomerates of catalyst particles and the ionomer (0.04 μm to several μm) [78]. In order to investigate the electrode layer structure, characterization of MEA of the anode materials was done before and after the fuel cell tests.…”
Section: Fuel Cell Performance Of Ptru-cnmsmentioning
confidence: 99%
“…CLs fabricated this way consist only of useful parts for 3-phase boundary: the catalyst, the electron conductor, the ion conductor and pores. The pores in the thin film layer can be defined as primary pores, which exist between catalyst particles (0.02-0.04 μm), and secondary pores, which exist between the agglomerates of catalyst particles and the ionomer (0.04 μm to micrometers) [173].…”
Section: Membrane-electrode Assembly Fabrication Historymentioning
confidence: 99%